Parental Involvement and Academic Self-Concept: A Comparative Study of Government and Private Secondary School Children - Soomro, Lubna Ahmed; Malik, Muniza (Progressive Research Journal of Arts & Humanities (PRJAH), 2022)
This study examined the relationship between the parental involvement and academic self- concept of the private and government secondary school students. Thus, it was hypothesized that the parental involvement would be a significant predictor of academic self-concept of children, and also that there would be the differences in parental involvement and academic self-concept of the private and government school children. The sample was consisted of two hundred participants, among them hundred were students of government schools, and similarly hundred were the private school children of grades 6th to 8th. The parental involvement scale was given to the parents and academic self-concept was administered on the children; and they also reported the involvement of their mother or father in such the studies. The age range was 11 to 14 years for children and of parents was 35 to 45 years. The results of the study indicated as the positive relationship of parental involvement with academic self-concept of school students. The parental involvement found as a significant predictor of the academic self-concept of students. The parents of the private school children found more involved than the parents of government schoolchildren. The implications discussed in terms of increasing awareness among government schools to involve the parents more in the studies of their children for better learning outcomes.